A case study analysis : Amway (M) Holdings Berhad / Asmahani Mohd Said, Nadiha Ismail and Sri Bayu Suradi - Mohd Said, Asmahani; Ismail, Nadiha; Suradi, Sri Bayu (Faculty of Business and Management, 2001)
Back to early 1976, with only 5 employees, a small office and a warehouse facility, Amway was established. Throughout almost three decades, Amway (M) Holdings Berhad has growth to its current position. Historically, it was incorporated on 30th August 1995 and was listed a year later, which was on the 15th of April 1996.